Application of vortex-assisted solid-phase extraction for the simultaneous preconcentration of Cd(ii) and Pb(ii) by nano clinoptilolite modified with 5(p-dimethylaminobenzylidene) rhodanine. Issue 31 (23rd July 2019) - Jouki, Ali; Rastegarzadeh, Saadat; Zendehdel, Mojgan; Zargar, Behrooz
Abstract : Herein, a simple, fast and reliable method based on vortex-assisted solid-phase extraction (VA-SPE) followed by flame atomic absorption spectrometry was developed for the simultaneous preconcentration and trace detection of cadmium and lead. Abstract : Herein, a simple, fast and reliable method based on vortex-assisted solid-phase extraction (VA-SPE) followed by flame atomic absorption spectrometry was developed for the simultaneous preconcentration and trace detection of cadmium and lead. Nano-sized clinoptilolite as a natural zeolite was modified with 5( p -dimethylaminobenzylidene) rhodanine and used as an adsorbent in the VA-SPE procedure. The modification process was assisted by the preliminary formation of a nano clinoptilolite-ZnO composite. The adsorbent was characterized by various techniques including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Under optimized conditions, the adsorbent exhibited good sorption potential as compared to nano clinoptilolite and nano clinoptilolite–ZnO composite. The calibration curves were linear in the range of 5–100 and 20–120 ng mL −1 for Cd(ii ) and Pb(ii ), respectively. The limit of detection for Cd(ii ) and Pb(ii ) was 1.0 and 6.5 ng mL −1, respectively. This method was successfully applied to the determination of cadmium and lead in fish, rice and water samples.